High precision synchronous acquisition of multi-source data for road roughness detection - Chen Xiaoyu; Chen Xuelei (Dianzi Jishu Yingyong)
With the increase in usage years, road surface damage such as unevenness occurs, and fast and effective road roughness detection equipment is urgently needed to detect the road. In this paper, we design a multi-sensor data synchronization acquisition system for road roughness detection, with FPGA as the control core, using NEMA data output from GPS and high stability crystal to establish a high-precision time reference, and using A/D sampling to synchronize data acquisition of 4 sensors. To improve the anti-interference capability and data sampling accuracy of the system, the sensor signal conditioning circuit is designed with differential amplification and anti-alias filtering. The experimental results show that the system completes the multi-sensor data synchronization acquisition with high precision, the time synchronization accuracy is microsecond level, can provide high precision raw data for evaluating the road roughness, has the advantages of high data sampling accuracy, good stability, strong anti-interference ability, low cost, etc., and has been successfully applied to the road detection vehicle of Wuhan XROE Co., ltd.